Copper-polydopamine composite coating decorating UHMWPE fibers for enhancing the strength and toughness of rigid polyurethane composites - Ming Feng (Elsevier, 2021)
In this study, ultra-high molecular weight polyethylene (UHMWPE) fibers reinforced rigid polyurethane (RPU) composites were prepared with the goal of improving strength and toughness. The satisfactory mechanical properties of the composites were mainly contributed to the copper-polydopamine composite coating. Polydopamine on the surface of UHMWPE fibers could react with polyurethane to form chemical bonds, leading to the improvement of material strength. Moreover, the deposited metal layer provided more paths for crack propagation in the composites, thus improved the toughness of the material. Compared with pure RPU, the tensile, interlaminar shear, and impact strength of polydopamine (PDA)-cooper (Cu) UHMWPE fibers/RPU composites were increased by 97.8%, 35.85%, and 2456.9%, respectively.